2022
DOI: 10.3389/fimmu.2022.872252
|View full text |Cite
|
Sign up to set email alerts
|

m6A Reader Igf2bp1 Regulates the Inflammatory Responses of Microglia by Stabilizing Gbp11 and Cp mRNAs

Abstract: Microglia are brain resident cells that function as brain phagocytic macrophages. The inflammatory responses of microglia induced by pathologic insults are key regulators in the progression of various neurological disorders. Currently, little is known about how these responses are regulated intrinsically. Here, it is observed that LPS-activated microglia exhibit distinct N6-methyladenosine (m6A) methylation patterns that are positively correlated with the expression patterns of corresponding mRNAs. High-throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…More important, these types of cells are with high heterogeneity. We, together with other independent groups, have demonstrated the distinct mRNA m6A signatures of brain tissues 126 and specific cell types including microglia 46 , 127 under pathological conditions (e.g., hypoxia, neuroinflammation). Similarly, mRNA m7G profiles are highly likely to be altered during neurodevelopment and the progressions of neurological disorders, which can be addressed by m7G MeRIP-seq and other high-throughput analyses.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…More important, these types of cells are with high heterogeneity. We, together with other independent groups, have demonstrated the distinct mRNA m6A signatures of brain tissues 126 and specific cell types including microglia 46 , 127 under pathological conditions (e.g., hypoxia, neuroinflammation). Similarly, mRNA m7G profiles are highly likely to be altered during neurodevelopment and the progressions of neurological disorders, which can be addressed by m7G MeRIP-seq and other high-throughput analyses.…”
Section: Introductionmentioning
confidence: 55%
“… 44 Our recent RNA-seq analyses also suggested significant up-regulation of Trmt112 expression in differentiating neural stem cells, 128 and reduction of expression levels of Wbscr22 transcripts in activated microglia. 46 These results provide confidence to clarify the contribution of the deregulation of WBSCR22/TRMT112 expression and rRNA m7G modification disorder on brain development and diseases in future studies.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Meanwhile, genetic and pharmacological inhibition of METTL3, a typical m6A writer, attenuated renal injury and inflammation [68,69]. IGF2BP1 is one of the common m6A readers but has not been reported in septic AKI; however, studies confirmed that its level could be elevated when induced by LPS and regulate the inflammatory responses [24,70]. In addition, IGF2BP1 was previously reported to promote proliferation in vitro and growth in vivo in an m6A-dependent manner [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that METTL3 promotes lipopolysaccharide (LPS)-induced microglial inflammation by activating the TNF receptor associated factor 6 (TRAF6)-NF-κB pathway ( Wen et al, 2022 ) and improves neuronal apoptosis and microglial activation by inactivating MyD88/NF-κB pathway ( Chen Y. et al, 2022 ). In addition, m6A reader Igf2bp1 is reported to regulate the inflammatory processes of microglia via enhancing the m6A methylation and stabilizing Gbp11 and Cp mRNAs ( Ding et al, 2022 ). It is reported that microRNA-421–3p could prevent inflammatory response in cerebral ischemia/reperfusion injury through targeting m6A reader YTHDF1 to inhibit p65 mRNA translation, which may provide a target for ischemia treatment ( Zheng et al, 2020 ).…”
Section: Effect Of Rna M6a Methylationmentioning
confidence: 99%